'n Politieke tegnologie van die vroeê Christen se gepynigde liggaam - Vorster, Johannes N. (Verbum et ecclesia, 2001)
The early Christian martyr is usually only seen in terms of testimony or witness. It is argued that a political technology of the body enables us to see the manner in which the pained body of the early Christian martyr functioned as a space upon which political strategies for the empowerment of interested parties were enacted.